Anti-Modernism as Reflected in the Main Character of Movie Into the Wild - Lilly Juniar Ibrahim; Magdalena Baga; Farid Muhamad (Transbahasa, 2026)
This study aims to examine how Into the Wild represents anti-modernism through the character of Christopher McCandless. The research employs a qualitative descriptive method using the sociology of literature approach to analyze how social conditions, family background, and personal experiences influence the main character’s rejection of modern values. The data were collected from the film’s script, scenes, and dialogues, supported by relevant academic sources. The findings indicate that anti-modernism is represented through Christopher McCandless’s rejection of material success, career ambition, institutional identity, and rational planning. His perspective develops gradually as a result of emotional conflict, family instability, and dissatisfaction with modern social structures. The contrast between Annandale as a structured suburban environment and Alaska as a natural and isolated setting highlights the tension between modern institutional life and the search for authenticity. The study also identifies key anti-modernist elements, including criticism of modern society, pessimism toward material values, appreciation of nature, resistance to institutions, and rejection of rational control. The study concludes that anti-modernism in the film functions both as a critique of modern life and as a reflection of its consequences, showing that complete withdrawal from society may lead to isolation and vulnerability.